Let's make an equation!

#1

I’ll start with y=x. You can either:

  • Multiply x by a number (y=3x)

  • Add or subtract a number from the previous equation (y=3x+2)

  • Add an exponent to x (y=3x^2+2)

  • Add a trigonometric function to x (y=sin(3x)^2+2)

  • All your other dreams!

y=x.

#2

y=x-x

#3

y = J1(x-x)

#4

y = csch(J1(x-x))

#5

y = csch(J1(x-x))/254

#6

y = csch(J1(x-x))/254+5943

#7

(csch(J1(x-x))/254+5943) / (csch(J1(x-x))/254+5943)

#8

((csch(J1(x-x))/254+5943) / (csch(J1(x-x))/254+5943))/((csch(J1(x-x))/254+5943) / (csch(J1(x-x))/254+5943))

#9

((csch(J1(x-x))/254+5943) / (csch(J1(x-x))/254+5943))/((csch(J1(x-x))/254+5943) / (csch(J1(x-x))/254+5943))^(pi)

#10

((csch(J1(x-x))/254+5943) / (csch(J1(x-x))/254+5943))/((csch(J1(x-x))/254+5943) / (csch(J1(x-x))/254+5943))^(pi+e)

#11

y = sec((csch(J1(x-x))/254+5943) / (csch(J1(x-x))/254+5943))/((csch(J1(x-x))/254+5943) / (csch(J1(x-x))/254+5943))^(pi+e))

#12

y = d/dx(sec((csch(J1(x-x))/254+5943) / (csch(J1(x-x))/254+5943))/((csch(J1(x-x))/254+5943) / (csch(J1(x-x))/254+5943))^(pi+e)))

#13

y = (d/dx(sec((csch(J1(x-x))/254+5943) / (csch(J1(x-x))/254+5943))/((csch(J1(x-x))/254+5943) / (csch(J1(x-x))/254+5943))^(pi+e))))+5943

#14

y = ∫((d/dx(sec((csch(J1(x-x))/254+5943) / (csch(J1(x-x))/254+5943))/((csch(J1(x-x))/254+5943) / (csch(J1(x-x))/254+5943))^(pi+e))))+5943)dx

#15

y = ∫((d/dx(sec((csch(J1(x-x))/254+5943) / (csch(J1(x-x))/254+5943))/((csch(J1(x-x))/254+5943) / (csch(J1(x-x))/254+5943))^(pi+e))))+5943)dx - 118

#16

y = sqrt(∫((d/dx(sec((csch(J1(x-x))/254+5943) / (csch(J1(x-x))/254+5943))/((csch(J1(x-x))/254+5943) / (csch(J1(x-x))/254+5943))^(pi+e))))+5943)dx - 118)

#17

y = (sqrt(∫((d/dx(sec((csch(J1(x-x))/254+5943) / (csch(J1(x-x))/254+5943))/((csch(J1(x-x))/254+5943) / (csch(J1(x-x))/254+5943))^(pi+e))))+5943)dx - 118))/2062

#18

y = ln((sqrt(∫((d/dx(sec((csch(J1(x-x))/254+5943) / (csch(J1(x-x))/254+5943))/((csch(J1(x-x))/254+5943) / (csch(J1(x-x))/254+5943))^(pi+e))))+5943)dx - 118))/2062)

#19

hi yes we have \LaTeX now

The last iteration I can comprehend is this:
y=\frac{\operatorname{csch}\left(J_1\left(x-x\right)\right)}{254}+5943 although it looks like for a few versions we just stacked the thing on itself a few times over

#20

This got way too complicated :dizzy_face:

4 Likes